Review on the Development of Conservation Area System in Indonesia - Agus Setiawan; Hadi S Alikodra (Media Konservasi, 2001)
lndonesia is categorized as one of the biodiversity centers in the world. The value of biological diversity as environmental, economic and social resources for maintaining the integrity and sustainability of natural systems and human life is very important. But, in other side, human development and thepopulation increase have caused the high rate of extinction of various plant and animal species. This high rate of extinction calls for a very serious and prompt action of conservation. Priority should be given to designing protected area for protection of species and ecosystem. Quantitatively, conservation development programs of Indonesia have a great achievement by designating 385 protected area which covering 22 560 545.46 ha. This paper overviews the development of protected area in lndonesia including systems, history, existing distribution, problems and obstacles, and government policy.